2017
DOI: 10.29038/2220-7481-2017-03-163-168
|View full text |Cite
|
Sign up to set email alerts
|

The State of Functional Capacity and Health of Students of Higher Educational Institutions

Abstract: The relevance of the research lies in the fact that the individualization of students' physical education has occupied a prominent place in scientific studies. The goal of the research is to study the state of the functional capacity and health of students of higher educational institutions. Materials and methods of the research: аnalysis and generalization of literary resources, testing and surveys. Results are as follows: the average group parameters of systolic and diastolic blood pressure level of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
2
1
Order By: Relevance
“…Analyzing the indicators of students' BMI and comparing them with the WHO recommendations, we can state that the body weight of about 57% of boys is normal, and the BMI of 43% of boys exceeds 25, which indicates overweight. Such data confirm the results of studies by P. Marynchuk [4] and O. Sabirov [5], but differ significantly from the data of Kazimov M.A. [8].…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Analyzing the indicators of students' BMI and comparing them with the WHO recommendations, we can state that the body weight of about 57% of boys is normal, and the BMI of 43% of boys exceeds 25, which indicates overweight. Such data confirm the results of studies by P. Marynchuk [4] and O. Sabirov [5], but differ significantly from the data of Kazimov M.A. [8].…”
supporting
confidence: 87%
“…The circumference of the chest among boys averages 93.2 cm. This is confirmed by a number of scientists [4][5][6]8].As a result of the analysis of the obtained data, we found that the average circumference of the chest of girls reaches 86.4 cm, which confirms the data of the literature [6 -8]. According to Erisman's calculations, we found that there were 20% of boys with normal chest width and 80% with narrow chest, which may indicate on stooping or frequent colds on the one hand, and underdevelopment of elm mass on the other.Especially in a coronavirus pandemic.…”
supporting
confidence: 66%
See 3 more Smart Citations